قواعد فقہیہ اور ضوابط فقہیہ: توضیح ، فرق، بنیادیں، اہمیت اور حجیت اور اصولی حیثیت کا تحقیقی تجزیہ: Juristic Rules and Principles: An Analytical Study of Explanation, Differences, Foundations, Importance, and Legal Status - Abdul Ghaffar; Dr. Muhammad Nawaz Al-Hasni (AL-IDRAK JOURNAL, 2024)
The study of Juristic Rules (Qawaid Fiqhiyyah) and Principles (Dawabit Fiqhiyyah) holds significant importance in the field of Islamic jurisprudence. These two concepts serve as the guiding principles for the application of Islamic law in various scenarios. This paper provides a comprehensive analytical study of the definitions, differences, foundations, importance, and legal status of Qawaid Fiqhiyyah and Dawabit Fiqhiyyah.The concept of Qawaid Fiqhiyyah refers to the general principles that govern Islamic legal rulings, which are derived from the Quran, Sunnah, Ijma' (consensus), and Qiyas (analogy). Dawabit Fiqhiyyah, on the other hand, refers to the specific, detailed guidelines that apply to particular circumstances within the broader context of Islamic law. This paper explores how both sets of principles interact, their basis in Islamic legal sources, and how they influence modern Islamic jurisprudence. The paper further discusses the importance of these principles in ensuring consistency, flexibility, and justice in the application of Islamic law. It also explores their legal status within the Islamic legal framework and their role in resolving legal issues in contemporary society. By examining these principles from both a historical and modern perspective, this study aims to highlight their relevance in contemporary Islamic jurisprudence and their role in shaping legal rulings in diverse contexts.